MODEL BANK SAMPAH INDUK KOTA PALEMBANG DALAM PERSPEKTIF EKONOMI SYARIAH DAN POTENSI PEMBERDAYAAN MASYARAKAT - Andiwijaya; Purwandari, Elce (IAIN Ambon, 2024)
This study aims to analyze the model of the Main Waste Bank in Palembang from the perspective of syariah economics and the potential for community empowerment. The research uses a qualitative approach with a case study design. This study identifies three main models in waste bank management: management, financing, and empowerment models. The findings show that the management model of the Bank Sampah in Palembang is operating well, but it needs continuous evaluation and improvement to enhance efficiency and effectiveness. The financing model still relies on community and government funds, highlighting the need for innovation in finding more sustainable financing sources. Meanwhile, the potential for community empowerment through the Bank Sampah is significant, yet it has not been fully maximized. Therefore, more structured and sustainable empowerment programs are necessary. This study recommends enhancing collaboration between the public and private sectors, applying syariah economic principles in financing, and developing more inclusive empowerment programs. The implications of these findings are expected to improve the sustainability and social-economic impact of the Waste Bank in Palembang.